SSEA-4 Antigen Is Expressed on Rabbit Lymphocyte Subsets - Jaromír Vašíček; Andrej Baláži; Miroslav Bauer; Peter Chrenek (Magnetochemistry, 2021)
SSEA-4 antigen can be mainly found in embryos and embryonic stem cells. However, its expression has been observed also in adult stem and progenitor cells, or even in some differentiated cells. Moreover, we found a considerable number of SSEA-4 positive (SSEA-4+) cells within the rabbit peripheral blood and bone marrow mononuclear cells (PBMCs and BMMCs) in our previous study. Since no information about such cells can be found anywhere in the literature, the aim of this study was to identify their origin. At first, phenotypic analyses of fresh rabbit PBMCs and BMMCs were performed using flow cytometry and specific antibodies against SSEA-4 and leukocyte subsets. Then, SSEA-4+ were enriched using magnetic activated cell sorting (MACS) and analyzed for their phenotype using qPCR. We found significant SSEA-4+ cell population in PBMCs (~50%) and BMMCs (~20%). All those cells co-expressed CD45 and a majority of them also expressed B-cell marker (IgM; 50% of SSEA-4+ PBMCs and 60% of SSEA-4+ BMMCs). Increased (p < 0.05) expression of SSEA-4, CD45 and B-cell markers (IgM, CD79α and MHCII) were also noticed by qPCR in SSEA-4+ cells enriched via MACS (with efficiency over 80%). Both methods did not detect significant expression of monocyte or T-cell markers. In conclusion, SSEA-4+ cells in rabbit blood and bone marrow are of hematopoietic origin and probably belong to B-lineage cells as possessing the phenotype of B lymphocytes. However, the true function of SSEA-4 antigen in these cells should be explored by further studies.